Policies for control and prevention of infections related to healthcare assistance in Brazil: a conceptual analysis - Hadelândia Milon de Oliveira; Cristiane Pavanello Rodrigues Silva; Rúbia Aparecida Lacerda (SciELO, 2016)
Abstract This article is a theoretical-reflexive study that aims to discuss the development and changes in the quality of healthcare assistance to the patient over the years in Brazil, in light of the policies of control and prevention of Healthcare-associated Infection (HAI). Aspects of HAI and the process of change in health policy in Brazil, as well as the quality of assistance associated with its control, are approached in relation to policies of patient safety. There are various new theoretical and practical proposals created in Brazil. In spite of the difficulty of measuring patient safety, directed to the prevention and control of HAI, we emphasize that to only create policies and establish norms, guidelines, and indicators is not sufficient. If no structural support or conditions exist for interventions in the practices of healthcare professionals, aiming at results in acceptable levels, the control of HAI will not be achieved.